On 2-Absorbing Submodules - M.Ali, Inaam; A. Harfash, Abdurehman (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Let R be a commutative ring with 10 and M is a unitary R-module . In this paper , our aim is to continue studying 2-absorbing submodules which are introduced by A.Y. Darani and F. Soheilina . Many new properties and characterizations are given .